Atmospheric extinction related to aerosol mass concentration and meteorological conditions in the atmosphere of Qena (Egypt) - EL-SHAZLY, SAYED M.; ABDELMAGEED, ABDELAZEEM M.; HASSAN, GAMILY; NOBI, BADRY (MAUSAM, 1991)
The dependence of the atmospheric extinction on aerosols concentration, temperature and wind speed is demonstrated. The atmospheric extinction was determined by measuring the transmission loss of radiation from alight source across 36 cm path with a photocell detector Conclusion include a general association of high extinction with high aerosols concentration, temperature and wind speed, but there are no one-to-one relationships. A correlation study between the extinction coefficient and each of these parameters was performed.